2017
DOI: 10.3390/ijms18010109
|View full text |Cite
|
Sign up to set email alerts
|

The Cause of Death of a Child in the 18th Century Solved by Bone Microbiome Typing Using Laser Microdissection and Next Generation Sequencing

Abstract: The history of medicine abounds in cases of mysterious deaths, especially by infectious diseases, which were probably unresolved because of the lack of knowledge and of appropriate technology. The aim of this study was to exploit contemporary technologies to try to identify the cause of death of a young boy who died from a putative “infection” at the end of the 18th century, and for whom an extraordinarily well-preserved minute bone fragment was available. After confirming the nature of the sample, we used las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Indeed, several reports have demonstrated that microbial alterations (or dysbiosis) can be found in an increasing number of human diseases and that their entities may be associated with the severity of the phenotype or with the sensitivity to specific therapies [1,2,3,4,5,6,7,8]. Thus, even if it has not been well established yet whether the microbiome alterations are the cause or the consequence of diseases, their study is intriguing since it opens the way to the identification of novel disease-specific biomarkers, or to the development of targeted therapies aiming to manipulate the microbiome in the attempt to restore a healthy status [9,10,11,12,13,14,15,16,17]. Next generation sequencing-based approaches have assessed their reliability in metagenomic studies escalating the possibility to describe microbial communities in detailand obtain both qualitative and quantitative information [1,2,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several reports have demonstrated that microbial alterations (or dysbiosis) can be found in an increasing number of human diseases and that their entities may be associated with the severity of the phenotype or with the sensitivity to specific therapies [1,2,3,4,5,6,7,8]. Thus, even if it has not been well established yet whether the microbiome alterations are the cause or the consequence of diseases, their study is intriguing since it opens the way to the identification of novel disease-specific biomarkers, or to the development of targeted therapies aiming to manipulate the microbiome in the attempt to restore a healthy status [9,10,11,12,13,14,15,16,17]. Next generation sequencing-based approaches have assessed their reliability in metagenomic studies escalating the possibility to describe microbial communities in detailand obtain both qualitative and quantitative information [1,2,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These techniques have impacted every field of molecular research, escalating previously used sequencing technologies [ 11 ], and opening the way to the -omic sciences foundation [ 1 , 2 ]. Indeed, NGS methods allow the sequencing of entire genomes [ 12 , 13 , 14 , 15 ], of exomes [ 16 , 17 , 18 ], of panels of genes related to a disease of interest [ 19 , 20 , 21 ], or of a single gene [ 22 , 23 , 24 , 25 , 26 ], but can also be used to explore the entire transcriptome [ 27 , 28 , 29 ], small RNAs [ 30 , 31 , 32 ], the epigenome [ 33 , 34 ], and the microbiome [ 35 , 36 , 37 , 38 ].…”
Section: High-throughput Analysesmentioning
confidence: 99%
“…In addition to the study of sequence variations at the DNA level, NGS methods can be used to study genetic variability, and the mechanisms underlying the onset of specific diseases at epigenetic, transcriptomic and metagenomic levels [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Indeed, several factors, other than individual genetic predisposition, such as diet, environmental factors and lifestyle, can influence the epigenome, the transcriptome and the microbiome [ 2 , 50 ].…”
Section: High-throughput Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these technological advances, a plethora of studies have been carried out to characterize the microbial communities of specific environments, including human beings [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In particular, the mutually beneficial relationship between the microbiome and the human host has been largely investigated [ 2 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%